Signature Pedagogy and Beyond: Reflections on Baltrinic and Wachter Morris (2020 - L. DiAnne Borders PhD (Teaching and Supervision in Counseling, 2020)
In a response to Baltrinic and Wachter Morris (2020), I expand on the term signature pedagogy and illustrate how clinical supervision satisfies the criteria for this designation in the counseling field. I then suggest an alternative term, “pedagogical foundations” (from Baltrinic and Wachter Morris), to ground work towards the authors’ goals of asking the ‘right questions’ about the ‘best things’ underlying counselor education practices and research. Finally, I outline some additional avenues (toward the same goals) via explorations of traditional learning theories and science of learning principles that emphasize student learning processes in the classroom - how students learn.
Keywords: signature pedagogy; clinical supervision; pedagogy; science of learning